Musical Instruments [1876] - Engel, Carl, 1818-1882 (Salt Lake City, UT : Project Gutenberg, 2017)
"Musical Instruments" by Carl Engel is a historical account written in the late 19th century. The work provides a detailed exploration of various musical instruments, tracing their origins and evolution across different cultures and time periods. It delves into the construction and characteristics of musical instruments from prehistoric to ancient civilizations, offering insights into the artistry and cultural significance surrounding music throughout history. The opening of the book outlines the universal appreciation of music as one of the fine arts and discusses the early development and diversity of musical instruments among various cultures. Engel highlights the ingenuity with which different materials have been used to create instruments, from wood and metal to animal hides. He also emphasizes the cultural significance of these instruments, noting how they reflect the distinctive characteristics of their origins and how studying them can provide valuable insights into the musical practices of different peoples, both past and present. (This is an automatically generated summary.)
Release date is 2017-04-11
E-text prepared by Anita Hammond, Wayne Hammond, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Musical instruments